Analisa Pemasangan Insulator Pada GSW/Kawat Tanah Tower Transmisi 150 KV Di PT PLN (Persero) P3B Sumatera - Cecep Zaenal Mutaqin; Fri Murdiya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
PT. PLN (Perseo) P3BS is part of PT PLN (Perseo) which specializes in high voltage and extra high voltage Overhead Line Transmission in Sumatera Island. Overally PT PLN P3BS has several assets of transmission i.e transmission tower with total of 20.110 units. Most of towers high between 30-46 meters. However, many line outage because frome lightening strike to Overhead Line Transmission. The Sumatra island position in the tropical zona which is prone to suffer from lightning strike.The installation or modification of lightning protection need to improve the reliability of transmission from lightning strike. PT PLN (Persero) P3BS has been done several ways to minimize the disturbance caused by lightning strike, such as by modifying GSW in order to have self grounding and insulated to the tower.Study has been done to knowing information about advantages or disadvantages in the utilizing of insulators on GSW simulated using ATP-Draw, normal simulation and modified GSW simulation. Then, both models are exposing to the lightening impulse voltage with the amplitude of 10 kA to 200 kA respectively.The modified GSW earth grounding system with the addition of insulators provides more resistance to the back flashover on the insulators lines and the reliability is increased. In the end, this modified GSW will get the effective value when it is attached to the tower coordinates which have high lightening potensial.Keywords : high voltage and extra high voltage Overhead Line Transmission, lightning density, lightning impulse voltage, GSW, ATP Draw.